Study of Biochemical Parameters in Sera of Diabetes Mellitus DM (Type 1) Patients with Nephropathy and Myocardial Vascular Disease Complication Issue: - Saifullah, Perry H; Nida, Saad Mohammed; Raoof, Israa Burhan (Al-Nahrain Journal of Science, 2018)
Type 1 diabetes mellitus is a disease caused by the progressive and selective destruction, by autoimmune mechanisms, of pancreatic beta cells. The aim of this study was to detecting antibodies against DNA in Type 1 Diabetes mellitus DM patients with nephropathy and myocardial vascular disease complication the Study was done of 80 samples of blood and serum of woman were obtained under fasting conditions and they divided as:20 samples of patients of DM, DM with CV, DM with Nephropathy and Subjects as control group in National Diabetes Center (NDC), with average age about (13-67) years to measure level of lipid, urea, glucose-6-phosphate dehydrogenase. The study showed elevated in level of lipid profile, urea in patients, auto immune antibody compared with control group